IMPROVEMENT OF FARMERS SKILL AND HOUSEHOLD INCOME THROUGH APPLICATION OF CLEAN, INTEGRATED AND SUSTAINABLE PRODUCTION ON HORTICULTURE AND CASSAVA COMMODITIES - Mulyaningsih, Yanyan (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Sustainable plant cultivation is an effort to increase productivity by applying environmentally friendly technology and the efficiency of production facility utilization and product processing with no or less waste or clean production. The objective of this activities are to improve farmer’s skill in vegetable and cassava cultivation and processed them to half-process product into food product which are highly nutritious, safe, and preferred by consumers. This activity involved Bojong and Sadar Tani Farmer Group at Bojongmurni Village, Ciawi District, Bogor Regency. The method used are extension, training, assistance and establishment of demonstration plot. Materials provided include the manufacture of organic fertilizer and mocaf, cultivation technique of vegetables and cassava, processing mocaf to food product and simple bookkeeping farming. Results showed that there was an improved awareness of training participants in the implementation of clean and sustainable production system in order to increase their income. This was shown from their enthusiasm in applying the knowledge they got in the trainings in this community service program.